Sleep detection with photoplethysmography for wearable-based health monitoring - Landström, Susanna (My University, 2021)
Remote health monitoring has gained increasing attention in the recent years. Detecting sleep patterns provides users with insights on their personal health issues, and can help in the diagnosis of various sleep disorders. Conventional methods are focused on the acceleration data, or are not suitable for continuous monitoring, like the polysomnography. Wearable devices enable a way to continuously measure photoplethysmography signal. Photoplethysmography signal contains information on multiple physiological systems, and can be used to detect sleep patterns. Sleep detection using wearable-based photoplethysmography signal offers a convenient and easy way to monitor health. In this thesis, a photoplethysmography-based sleep detection method for wearable-based health monitoring is described. This technique aims to separate wakefulness and asleep states with adequate accuracy. To examine the importance of good quality data in sleep detection, the quality of the signal is assessed. The proposed method uses statistical and heart rate based features extracted from the photoplethysmography signal. Using the most relevant features, various supervised learning algorithms are trained, compared and evaluated. These algorithms are logistic regression, decision tree, random forest, support vector machine, k-nearest neighbors, and Naive Bayes. The best performance is obtained by the random forest classifier. The method received an overall accuracy of 81 percent. It was able to detect the sleep periods with 86 percent accuracy and the awake periods with 74 percent accuracy. Motion artifacts occurring during the awake time caused distortion to the signal. Features related to the shape of the signal improved the accuracy of sleep detection, since signal distortion was associated with the awake time. It is concluded that photoplethysmography signal provides a good alternative for wearable-based sleep detection. Future studies with more comprehensive sleep level analysis could be conducted to provide valuable information on the quality of sleep.

Viime vuosina etänä tapahtuva terveyden seuranta on saanut yhä enemmän huomiota. Unen tunnistaminen antaa käyttäjille tietoa heidän henkilökohtaisista terveysongelmistaan ja voi auttaa erilaisten unihäiriöiden diagnosoinnissa. Tavanomaiset menetelmät käyttävät kiihtyvyyteen perustuvaa dataa, tai eivät ole soveltuvia jatkuvaan seurantaan, kuten polysomnografia. Puettavan teknologian avulla fotopletysmografiasignaalin jatkuva mittaus on mahdollista. Fotopletysmografiasignaali sisältää tietoa useista fysiologisista järjestelmistä ja sitä voidaan käyttää unen tunnistamiseen. Puettavan teknologian avulla mitatun fotopletysmografiasignaalin käyttö unen tunnistuksessa tarjoaa kätevän ja helpon tavan seurata terveyttä. Tässä diplomityössä kuvataan fotopletysmografiaan perustuva unenhavaitsemismenetelmä, joka soveltuu puettavaa teknologiaa hyödyntävään terveyden seurantaan. Tekniikalla pyritään erottamaan hereillä olo ja uni riittävän tarkasti. Signaalin laatu arvioidaan, jotta voidaan tutkia datan laadun tärkeys unen tunnistuksessa. Kehitetty menetelmä käyttää tilastollisia ja sykkeeseen perustuvia ominaisuuksia, jotka on erotettu fotopletysmografiasignaalista. Tärkeimpiä ominaisuuksia käyttämällä erilaisia valvottuja oppimisalgoritmeja koulutetaan, vertaillaan ja arvioidaan. Käytetyt algoritmit ovat logistinen regressio, päätöspuu, satunnainen metsä, tukivektorikone, k-lähimmät naapurit ja Naive Bayes. Paras tulos saadaan käyttämällä satunnainen metsä -algoritmia. Menetelmällä saavutetaan 81 prosentin kokonaistarkkuus. Uni pystytään tunnistamaan 86 prosentin tarkkuudella ja hereillä olo 74 prosentin tarkkuudella. Hereillä ollessa liikkeestä johtuvat häiriöt aiheuttavat vääristymää signaaliin. Signaalin muotoon liittyvät ominaisuudet paransivat unentunnistuksen tarkkuutta, koska signaalin vääristyminen yhdistettiin hereilläoloaikaan. Tutkimuksen tuloksista voidaan tehdä johtopäätös, että fotopletysmografiasignaali tarjoaa hyvän vaihtoehdon puettavaa teknologiaa hyödyntävään unen tunnistamiseen. Tulevaisuudessa unen eri vaiheita voitaisiin tutkia kattavammin, jolloin saataisiin arvokasta tietoa unen laadusta.
Keywords: classification, health monitoring, photoplethysmography, sleep detection, supervised learning, wearables